Impact Social Samen Leven 's Actions in the Perspective of Bugis Community Customary Criminal Law Rules - Salsabila, Alifah Nurghina; Jasmaniar, Jasmaniar; Tjolleng, Arfah (HORIZON PUBLIC LEGAL STUDIES, 2025)
This research aims to know and understand the regulation of customary criminal law of the Bugis community against samen leven acts that violate customary norms and to know and understand the social impact on samen leven offenders in society. This research uses normative research methods, namely the type of research conducted by analyzing legal rules. This type of research is conducted by means of a literature study, namely by reading and analyzing written materials. The results show that customary criminal law still plays a role in upholding the norms of decency in society, especially in dealing with the phenomenon of samen leven . In Bugis society, the value of Siri'na Pacce reinforces the view that this behavior tarnishes honor and social balance, so customary sanctions are still applied even though national law has regulated it in the Criminal Law Code. In addition to being socially stigmatized, samen leven perpetrators also face impacts such as family disharmony and unclear child status. Therefore, customary law is still considered relevant in resolving cases culturally and maintaining social harmony in society. The recommendations of this research are 1. Socialization of the negative impact of samen leven and the importance of customary norms and laws need to be improved through education, media and communities so that the younger generation understands the consequences. 2. A policy that harmonizes customs and national laws is needed, so that the settlement of samen leven cases still consider cultural aspects, justice and protection for all parties.